Social and economic assessment of the development of tourism sphere in the Karaganda region - Zhekenov, S.S.; Takzhanov, S.A. (Fundamental and Experimental Biology, 2022)
Today, a lot of work is being done at the republican and regional levels to attract foreign tourists to Kazakhstan. In the Karaganda region, the activities in the sphere of image policy and popularization of tourist achievements of the region are implemented. The problem of improving the strategic management of the development of the tourism industry requires increase of interest to the research characterizing the relevance of the topic. Particularly, the problem of strategy formulation has not been fully solved, standards and indicators of the effectiveness of the tourism development strategy have not been formulated, the problem of measuring and differentiating the influence of external and internal factors on the implementation of the adopted strategy has not been considered, and there is no effective mechanism for implementing the adopted strategy. This article describes the process of tourism development in the Karaganda region.